The Capitalization of Backpacking Tourism Culture in Indonesian Films - Agustinus Rusdianto Berto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
A film, as a media, acts significantly on popularizing the culture of backpacking tourism, which is closely related to the capitalist values. This research attempts to unveil the capitalist values in Indonesian backpacking films. The data are obtained by applying qualitative content-analysis to 2 (two) Indonesian films, namely Haji Backpacker and Laura Marsha. The analysis leads to several interesting findings. First, Indonesian backpacking films, either explicitly or implicitly, more-likely prefer foreign tourist destinations. Second, the backpacker ideologies are presented more obviously in the rather implicit backpacking movie, Laura Marsha, than in the more explicit one, Haji Backpacker. Third, films contribute in shifting the ideological meaning of backpacking, which now emphasizes on progress and recency (standardization), individualism (pseudo-individualization and social-cement), and efficiency (fetishism). Further researchers should analyze the effects of the shifting of the meaning from the perspective of the audience and content producers.